2010
DOI: 10.1111/j.1365-2044.2009.06228.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and risks of furosemide in acute kidney injury

Abstract: SummaryFurosemide, a potent loop diuretic, is frequently used in different stages of acute kidney injury, but its clinical roles remain uncertain. This review summarises the pharmacology of furosemide, its potential uses and side effects, and the evidence of its efficacy. Furosemide is actively secreted by the proximal tubules into the urine before reaching its site of action at the ascending limb of loop of Henle. It is the urinary concentrations of furosemide that determine its diuretic effect. The severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(132 citation statements)
references
References 73 publications
5
120
1
4
Order By: Relevance
“…In two recent metaanalyses [154,155], the administration of diuretics did not reduce the incidence and severity of AKI. For this indication, furosemide did not demonstrate any benefit in terms of in-hospital mortality, the need for and the number of sessions of RRT.…”
Section: (Grade 1−) Strong Agreementmentioning
confidence: 93%
“…In two recent metaanalyses [154,155], the administration of diuretics did not reduce the incidence and severity of AKI. For this indication, furosemide did not demonstrate any benefit in terms of in-hospital mortality, the need for and the number of sessions of RRT.…”
Section: (Grade 1−) Strong Agreementmentioning
confidence: 93%
“…Two meta‐analyses277, 278 and eleven RCTs were extracted. The results of both meta‐analyses indicated no effect on in‐hospital mortality rate and the need for blood apheresis as a result of furosemide administration, and no new RCTs have been completed to date.…”
Section: Cq12: Acute Kidney Injury/blood Apheresismentioning
confidence: 99%
“…Moreover, some observational studies have demonstrated associations between diuretics and death and renal nonrecovery in AKI (1,10). Many clinicians thus avoid diuretics in AKI because of concern that they may induce intravascular hypovolemia as well as exacerbate renal dysfunction and electrolyte abnormalities (11,12).…”
Section: Introductionmentioning
confidence: 99%